CuInS(2) quantum dot-sensitized TiO(2) nanorod array photoelectrodes: synthesis and performance optimization - Zhou, Zhengji (Springer, 2012)
CuInS(2) quantum dots (QDs) were deposited onto TiO(2) nanorod arrays for different cycles by using successive ionic layer adsorption and reaction (SILAR) method. The effect of SILAR cycles on the light absorption and photoelectrochemical properties of the sensitized photoelectrodes was studied. With optimization of CuInS(2) SILAR cycles and introduction of In(2)S(3) buffer layer, quantum dot-sensitized solar cells assembled with 3-μm thick TiO(2) nanorod film exhibited a short-circuit current density (I(sc)) of 4.51 mA cm(−2), an open-circuit voltage (V(oc)) of 0.56 V, a fill factor (FF) of 0.41, and a power conversion efficiency (η) of 1.06%, respectively. This study indicates that SILAR process is a very promising strategy for preparing directly anchored semiconductor QDs on TiO(2) nanorod surface in a straightforward but controllable way without any complicated fabrication procedures and introduction of a linker molecule.